2012
DOI: 10.1017/s0025315412001105
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing spatial patterns of molluscs in a eutrophic tropical bay

Abstract: Samples were collected from 10 stations distributed through three sectors in Guanabara Bay during two consecutive years, in order to determine factors that influence the spatial pattern of molluscs and to describe the structure and composition of this community in a eutrophic estuarine system on the Brazilian coast. Although only one species, the gastropodHeleobia australis, comprised 77% of mollusc abundance, 59 species were identified in the bay. In addition toH. australis, three other species were dominant:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 69 publications
1
15
1
1
Order By: Relevance
“…Differences in genera composition and abundances can be related to the method used to collect the mollusks (grab, trawl) and also depend on the sampling effort. We did not observe a clear relationship between sediment type and the genera composition of mollusks, which has been described in other malacological studies [41,42]; but we found that mollusks were related with dissolved oxygen (DO) concentrations near the seafloor (10% of total variance). The differences found could be due to the identification level (genus) while other studies have been done to species level.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Differences in genera composition and abundances can be related to the method used to collect the mollusks (grab, trawl) and also depend on the sampling effort. We did not observe a clear relationship between sediment type and the genera composition of mollusks, which has been described in other malacological studies [41,42]; but we found that mollusks were related with dissolved oxygen (DO) concentrations near the seafloor (10% of total variance). The differences found could be due to the identification level (genus) while other studies have been done to species level.…”
Section: Discussioncontrasting
confidence: 72%
“…A study performed in 2011 recorded 18 genera at 31 ∘ N which is the same latitude as TSB; in that study most stations were located at more than 200 m depth [27]. This genera abundance is low compared with the 36 genera collected in this study; however, it is low compared to tropical Guanabara Bay located in Brazil with 46 genera [41], but it is close to the subtropical Mersin Bay in Turkey with 35 genera [42].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Scale-dependent patterns of distribution may be particularly important in coastal areas, since they are characterized by variability in abiotic conditions (Neves et al, 2012). For benthic fauna, patterns of distribution are related to salinity (Atrill, 2002;Attrill and Rundle, 2002;Ysebaert et al, 2003), sediment characteristics (Teske and Wooldridge, 2003;Anderson et al, 2004) and other factors.…”
Section: Introductionmentioning
confidence: 99%